My street food kitchen fast and easy flavours from around the world - Joyce, Jennifer (Sydney Murdoch Books, 2015)
"The recipes in My street food kitchen represent a diverse and tantalising range of food discoveries, organised into regional chapters covering new American food; Mexico & South America ; the flavours of the Mediterranean ; the Middle East ; the best of China 7 Taiwan ; Japan & Korea ; South-East Asia ; and India"
Dirty Burgers and Crunchy Kaleslaw: New American food -- Fiery tacos and icy ceviche: Mexico and South America -- Agrodulce and Picante: the Mediterranean -- A spoonful of Aleppo pepper: the Middle East WC -- Hot and sour with special salt: China -- Miso tasty: Japan and Korea -- Imperial prawns and happy pancakes: South East Asia -- Chai and roti: India.
Keywords: International cooking